Palynological studies in the Łódź region: https://doi.org/10.26485/AGL/2017/106/10 - Balwierz, Zofia (Acta Geographica Lodziensia, 2018)
The new research methods that developed in the 20th century, useful for the studies of sediments and palaeogeographical reconstructions, have caused the need for specialists in these fields to arise. One of such methods is pollen analysis, whose centennial anniversary was celebrated in 2016. Its use in the studies of the sediments of the Quaternary was the decisive factor in employing a pollen analysis specialist by the Institute of Geography, University of Łódź. The article elucidates the history of palynology in Łódź, which, after two short episodes, lasted continuously, between the years 1972–2006 and to presents, very briefly, the problems connected with organizing the laboratory as well as to highlights the most important accomplishments of its employees.